Analysis on switching overvoltage and suppression method of cable joint in 500 kV cable line - Hongtao Ren (Elsevier, 2021)
The breakdown accident of cable joint occurs frequently when the sheath overvoltage cable line is closed, but the cable joint is ignored or simply treated in the previous overvoltage simulation of cable system. To solve this problem, a joint equivalent impedance model is established for a 500 kV cable line intermediate joint structure, and a 500 kV high voltage cable system simulation model considering the cable intermediate joint is built in the transient simulation software ATP-EMTP to simulate and calculate the switching overvoltage on the core and metal sheath of the cable intermediate joint, and to study the influence of different number of outgoing buses and residual charge of cable core The influence of some factors on the switching overvoltage of cable joint. In addition, the measures to restrain the switching overvoltage of cable joint are analyzed. The research results provide reference for the fault analysis of cable joint and the parameter design of cable insulation coordination.